2019
DOI: 10.1177/0161734619879859
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Echodynamography in Comparison with Particle-image Velocimetry

Abstract: Echodynamography (EDG) is a computational method to estimate and visualize two-dimensional flow velocity vectors by applying dynamic flow theories to color Doppler echocardiography. The EDG method must be validated if applied to human cardiac flow function. However, a few studies of flow estimated have compared by EDG to the flow data were acquired by other methods. In this study, EDG was validated by comparing the analysis of estimating and visualizing flow velocity vectors obtained by original particle image… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…Two studies, by Oktamuliani et al [ 65 ] and Shimizu and Ohta [ 66 ], presented hydrogels as a promising PIV channel material in cardiovascular research. Hydrogels can entirely replace standard materials such as silicon or PMMA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies, by Oktamuliani et al [ 65 ] and Shimizu and Ohta [ 66 ], presented hydrogels as a promising PIV channel material in cardiovascular research. Hydrogels can entirely replace standard materials such as silicon or PMMA.…”
Section: Discussionmentioning
confidence: 99%
“…The Scopus search revealed that only two studies performed cardiovascular PIV measurements using hydrogels as a channel material during the last 22 years. Oktamuliani et al [ 65 ] used PIV for visualizing flow velocity vectors based on a left ventricular phantom hydrogel. The phantom hydrogel was produced of PVA with a mixture of dimethyl sulfoxide (DMSO) and water.…”
Section: Hydrogels For Piv Channel Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such models provide good results, but their preparation is time-consuming, and they are relatively expensive to produce. Hydrogel phantoms possess transparency and parameters that are required to work with imaging-based measurement systems [ 12 ]. A review of different kinds of hydrogel groups was completed by [ 13 ], outlining different advantages and disadvantages.…”
Section: Introductionmentioning
confidence: 99%
“…Echodynamography is one method developed for CD vector field estimation, which separates the flow into 'base' and divergence-free flows to reconstruct the velocity vector field [17]. Although the 'base' flow is arbitrary and only performs well for rotating flows [18], it has been validated against PIV and used in research [19,20]. Pedrizzetti & Tonti introduced an alternative method using the irrotational flow assumption [21], but this formulation underestimates the strength of rotating flows [18].…”
Section: Introductionmentioning
confidence: 99%